The influence of FinTech on the EU legislation concerning the opening of payment accounts in EU regulated payment institutions - Konča, Nataļja (Riga Graduate School of Law, 2023)
payment facility. The FinTech projects hold a considerable share on the EU financial market. The Single Euro Payments Area (SEPA) system is one of the core elements in EU payment infrastructure, which makes EURO transactions cheaper and faster. Cross-border payments digitalisation was the main stimulus to EU FinTech innovation development. EU single payment ecosystem requires single payment account for every EU Member State resident in order to keep the equal rights to access the payment account with basic features. Customer due diligence, Know Your Customer policy and Risk-based Approach are significant instruments in order to prevent ML/TF, proliferation offences. This paper will guide through the EU regulative framework which forms the legal base for the EU FinTech institution procedures and policies establishment and development.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Financial law; FinTech